y = x^2+7x−4

y = −x−4

Y = x² + 7x - 4

y = -x - 4

x² + 7x - 4 = -x - 4

+ x + x

x² + 8x - 4 = -4

+ 4 + 4

x² + 8x = 0

x(x) + x(8) = 0

x(x + 8) = 0

x = 0 or x + 8 = 0

- 8 - 8

x = -8

y = -x - 4

y = -0 - 4

y = 0 - 4

y = -4

(x, y) = (0,4)

or

y = -x - 4

y = -(-8) - 4

y = 8 - 4

y = 4

(x, y) = (-8, 4)

The solutions are (0,4) and (8,4).

Y=x²+7x-4

y=-x-4

We can solve this system of equation by equalization method.

x²+7x-4=-x-4

x²+7x+x-4+4=0

x²+8x=0

x(x+8)=0

we have two linear equations :

x=0 ⇒ x=0 ⇒ y=-x-4=-0-4=-4

(x+8)=0 ⇒ x=-8 ⇒ y=-x-4=-(-8)-4=8-4=4

**We have two solutions:****solution₁: x=0; y=-4****solution₂: x=-8; y=4**